Novák's Lucerna and the Historiographical Problem of "Czech Modernism" - Locke, Brian (Intersections, 2005)
The opera Lucerna (premièred 1923) by the Czech composer Vitězslav Novák demonstrates the problematic position of Czech music in the historiography of the early twentieth century, since neither "avant-garde" nor "antimodernist" suffice for it as stylistic labels. A leader of Czech modernism during the fin de siècle, Novák's music embodies the aesthetic crisis his generation faced after 1918. Lucerna's score reveals a complex negotiation of multiple stylistic influences, including impressionism, folklore, and Strauss, paralleling the Czech community's hesitant acceptance of international modernism in the early interwar period. The opera's lack-lustre finale echoes the contemporaneous return to Czech traditional values, using Smetana as an anachronistic model for modernist opera.